PENGARUH PELATIHAN, PENGEMBANGAN, PENGAWASAN DAN KUALITAS KERJA TERHADAP KINERJA KARYAWAN PT. TRANS INTRA ASIA (STUDI KASUS PADA PROGRAM KOTA TANPA KUMUH) - Iis Tri Rahayu; Suyanto (OBOR: Oikonomia Borneo, 2021)
Employee performance is the result or level of success of a person as a whole during a certain period in carrying out tasks such as work standards, targets or goals, as well as other criteria that have been determined in advance and have been mutually agreed upon. The factors that influence performance are individual factors, namely abilities and skills, organizational support factors and management support factors. By holding training, development and supervision, employees are expected to be able to improve their performance in carrying out their duties and responsibilities properly. This research method is causal comparative by using quantitative analysis tools to determine the effect of training, development, supervision and work quality on employee performance. From the results of the analysis, it is known that the research instrument is declared valid with a probability significance level (p < 0.05) all variables are said to be reliable because the Cronbach alpha coefficient value (a > 0.60). The variables of training, development, supervision and work quality on employee performance each affect employee performance at the level of Sig t < probability (p < 0.05). The results of statistical tests state that simultaneously (simultaneously) the influence of training, development, supervision and work quality affects employee performance, namely the Fcount value of 12.012 while Ftable is 2.64 so that Fcount > Ftable and the significance value is at the 0.000 level at the 5% level. (p < 0.05). Thus it can be concluded that Ha is accepted and H0 is rejected